Removal of Methylene Blue Dye Using Low Cost Adsorbent - SIMI, A.; AZEEZA, V. (Asian Journal of Chemistry, 2010)
Adsorption is an impotent method for colour removal from wastewater. Batch experiments were conducted to assess the potential for removal of methylene blue from aqueous solution by adsorption on to Jack fruit carbon. The equilibrium isotherm was determined and plotted to obtain the Langmuir constants, the Freundlich constants and Peterson constants. It was observed that very short contact time upto 30 min was required for the system to attain equilibrium. The maximum adsorption capacity of Jack fruit carbon was found to be 0.1047 mg of dye/g of Jack fruit carbon.